Fish species, traders, and trade in traditional market: Case study in Pasar Baru, Balikpapan City, East Kalimantan, Indonesia - RAHMAN LATIF ALFIAN; JOHAN ISKANDAR; BUDIAWATI SUPANGKAT ISKANDAR; SUROSO; DICKY P. ERMANDARA; DEDE MULYANTO; Ruhyat Partasasmita (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Alfian RL, Iskandar J, Iskandar BS, Suroso, Ermandara DP, Mulyanto D, Partasasmita R. 2020. Fish species, traders, and trade in traditional market: Case study in Pasar Baru, Balikpapan City, East Kalimantan, Indonesia. Biodiversitas 21: 393-406. The purpose of this study is to analyze the species of fish traded by fish traders in the Pasar Baru traditional market, Balikpapan, East Kalimantan. In addition, this study analyses the Traditional Ecological Knowledge (TEK) of fish traders on fishes, including naming fish, fish habitat and caught technique, sex differentiate, taste of fish, price of fish, origin of fish and processing, freshness of fish and preservation, and the transmission of knowledge and conservation of the fish species. This study used qualitative methods that ethnoichthyology approach was used, with some field technics, namely observation, depth interview, and survey of species of fish were applied. The results showed that there were 36 species, representing 22 families recorded in the traditional market of Pasar Baru. Fish traders have good knowledge on fishes, including naming fish, sex differentiate, fish caught, freshness of fish, and how to preserve fish. Traders often offer fish to buyers by mentioning the names and various aspects of fish species, so the traders have indirectly introduced and socialized the TEK of fish species to buyers and a wider community. In addition, since the high diversity of fish species has normally traded in the traditional market, it has an important function not only for the community's economy, but also have an important function for the conservation of biodiversity of fish species in the region.